VIRTUAL LEARNING: PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Julaeha, Siti (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Information and Communication Technology (ICT) promotes any possibilities ofimprovement of the quality of instruction. Internet-based instruction or virtuallearning is an example of the implementation of ICT in instruction. Theintegration of virtual learning into the face-to-face instruction enables the qualityof instruction to improve, in addition to increase the eficiency and effectivity ofinstruction. There are factors that should be consider in integrating virtuallearning into the face-to-face instruction in order to achieve the qualityinstruction. Besides that, in order to make effective integration of virtual learninginto the face-to-face instruction, there should be changes in learning paradigm, aswell as in systems of work operation and structure of organization. Teachers’ andstudents’ ICT literacy are also required to make the success of the integartion ofvirtual learning into face-to-face instruction. This paper describe the definition ofvirtual learning, the advantages and the limitation of implementation of virtuallearning in instruction, as weel as the conditions that should be consider in orderto effectively integrate virtual learning into face-to-face instruction. Thedescription will be preceded by the development of ICT implementation ininstruction and ended by conclusion and recommendation.